Kinerja Digester Biogas Tahap Tunggal yang Mengolah Limbah Makanan pada Suhu Tropis - Fahmi, Nadya Yunisa; Priadi, Cindy Rianti; Hermansyah, Heri; Suharso, Arif Rakhman (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2025)
The degradation process of food waste with anaerobic digestion technology can be performed in a single-stage bioreactor. This study examined the effect of a single-stage digester configuration on biogas production using cow manure inoculum at a tropical ambient temperature of 27.3 ± 1 °C. The single-stage digester had a working volume of 369 L. Feeding food waste into the bioreactor was carried out 5 times a week with a maximum OLR of 0.8 Kg/day. The average biogas production was 90.6 L/day. Also, the results showed that applying a single-stage digester configuration in degrading food waste could produce a carbon recovery of 71.41% in the carbon mass balance analysis. These results indicate that the single-stage digester configuration performed well. The single-stage digester configuration gradually increased biogas production.